The Structure and Composition of Tampa’s Urban Forest - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
FOR-209, a 4-page illustrated fact sheet by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, presents the information gained about the distribution of vegetation and variety of species in Tampa’s urban forest from an urban ecological assessment conducted in the city of Tampa. Includes references. Published by the UF School of Forest Resources and Conservation, February 2009. Reviewed February 2012.